Impact of bedding planes, delay interval and firing orientation on blast induced ground vibration in production blasting with controlling strategies. (October 2022) - Agrawal, Anurag; Choudhary, B.S.; Murthy, V.M.S.R.; Murmu, Sunny
Highlights: Bench face orientation is very important for the safety of the nearby structures. Design the blast firing sequence in the opposite direction concerning to structures. Design the bench face across the strike of the rock bed. Signature hole waveforms analyzed to determine the blast delay sequence. Monte Carlo simulation and sensitivity analysis assisted in blast vibration control. Abstract: Traditional techniques of production blasting and delay timing patterns are restructured to minimise ground vibrations for the geological setting of Jharia coal field, a prime coking coal belt with densely covered habitat. Blasting techniques based on delay pattern and bench face orientation are proposed in this paper to protect the structures within a distance of 100 m from active bench face while maintaining daily production and charge per delay. Seventeen single representative blast holes (signature waveforms) were detonated in the last hole at the series of production blasts. When blast vibration was monitored in the opposite direction of the firing sequence and compared to the values in the same direction and behind the bench face, it was observed that the PPVs were less than 10 mm/s at 55 m radial distance. Also, when blast monitoring is setup near structures, across the strike of rock bed, blasting range can be designed 65 m away from structures rather than along the strike. The signature hole waveforms were generated using electronic delay detonators, and PPV values were controlled by maintaining delay intervals of 25 ms and 67 ms between holes and rows, respectively. Monte Carlo simulation (MCS) was used to generate the probabilistic data, and 5000 simulations helped to evaluate the volatility arising in the investigated blasting techniques, and it was concluded that the modified bench face design technique in 80 % of the cases generates PPV which is lower than the threshold value of 10 mm/s. The contribution to variance (CTV) and correlation coefficient (CC) approaches were used for the sensitivity analysis and it was observed that the bedding plane strike direction and radial distance are the two most critical factors impacting PPV. The proposed equation has shown high coefficient of determination (R 2 = 0.85) and low root mean square error (RMSE = 4.42) as compared to other four standard equations. Suggested blasting techniques can be of immense use for conducting production blasting in a safe and productive manner.